1986
DOI: 10.1073/pnas.83.23.9179
|View full text |Cite
|
Sign up to set email alerts
|

Expression of insulin-like growth factor II in human placentas from normal and diabetic pregnancies.

Abstract: The growth and development of the placenta is critical to fetal growth and development; however, little is known regarding the mechanisms controlling placental growth and development. Human placental membranes are known to possess receptors for insulin-like growth factors I and II (IGF-I and IGF-II) from early gestation, and increasing evidence supports a major role for IGF-I and/or IGF-II in fetal growth and development. Therefore, the IGFs may also play a significant role in regulating placental growth and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
3

Year Published

1989
1989
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 32 publications
(24 reference statements)
2
40
0
3
Order By: Relevance
“…Apart from the expression of mRNA for IGF-II in the placenta, which has been widely studied (Shen et al 1986, Reynolds et al 1997, few studies have investigated how pregnancy affects the expression of mRNA for IGF-II in non-reproductive tissues. The plasma levels of IGF-II were reduced in the pregnant dams as compared with the virginal animals in this study, which is in contrast to findings in a previous study performed in a similar animal model (Sohlström et al 1998a).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the expression of mRNA for IGF-II in the placenta, which has been widely studied (Shen et al 1986, Reynolds et al 1997, few studies have investigated how pregnancy affects the expression of mRNA for IGF-II in non-reproductive tissues. The plasma levels of IGF-II were reduced in the pregnant dams as compared with the virginal animals in this study, which is in contrast to findings in a previous study performed in a similar animal model (Sohlström et al 1998a).…”
Section: Discussionmentioning
confidence: 99%
“…Both IGFs-I and -II are synthesized in the placenta (6,7). As the localization of IGFs and IGFBPs was similar, it was suggested that the IGFBPs regulated IGFs within the placenta (8).…”
Section: Introductionmentioning
confidence: 97%
“…Placental poly(A)+ RNA from differing stages of gestation was separated by electrophoresis through 1% agarose/formaldehyde denaturing minihorizontal submarine slab gels, transferred to nitrocellulose, and baked under vacuum for 2 hr at 80°C as described (30). Total lines (32).…”
Section: Methodsmentioning
confidence: 99%